Analisis Pengaruh Parameter Hardening terhadap Distorsi Spesimen CT58 dengan Metode Taguchi - Kurniawan, Perwita; Sartoyo, Millenino Bergas; Nugraha, Aditya; Nugroho, Adi (JMPM (Jurnal Material dan Proses Manufaktur), 2023)
This research discusses the problem of distortion of cigarette engine components after the hardening process. This research focuses on changes in the dimensions of the hole diameter, gap width, and flatness of the components. The austenite temperature, quench medium, and tempering temperature were examined to determine their effect on distortion. Components are made of machine steel group S45C equivalent to AISI 1045. This study used a specimen named CT58 with Austenite temperature variations of 820 ̊C 840 ̊C 860 ̊C, then variations of oil, oil + water, and water quenching media and Tempering temperature variations of 200 ̊C, 250 ̊C, and 300 ̊C. This research used the Design of Experiment, followed by statistical analysis using the Minitab application. The results showed that the distortion in the CT58 specimen was most affected by the Austenite temperature, followed by the Quench medium and Tempering temperature. The austenite temperature of 820°C, the oil quench medium, and the tempering temperature of 250°C are the best hardening parameters for the Inner Diameter aspect. The austenite temperature of 820°C, oil quench media, and tempering temperature of 250°C are the best setting parameters for the Gap Width aspect. The austenite temperature of 820°C, oil quench media, and tempering temperature of 250°C are the best setting parameters for the Flatness aspect